2008
DOI: 10.1007/s11661-008-9680-5
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Mystery of Harper–Dorn Creep in Metals

Abstract: In the present investigation, the occurrence of Harper-Dorn creep in Pb was studied under the condition of large strains. In performing the study, two Pb grades, commercial-purity Pb (99.95 pct) and high-purity Pb (99.999 pct), were creep tested at 573 K. The mechanical data showed that 99.95 Pb, unlike 99.999 Pb, did not exhibit accelerated creep rates at stresses <0.1 MPa (the region of Harper-Dorn creep). Also, the data on 99.999 Pb revealed that the creep curves associated with Harper-Dorn creep exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 32 publications
(72 reference statements)
3
15
0
Order By: Relevance
“…After a short transient stage due to elastoplastic deformation, the impression creep reaches a steady state similar to the compression creep test with sudden jumps in the impression curves during the steady state impression creep. The sudden jumps in the impression curves are similar to that for the impression creep of single crystal Pb without the passing of electric current [13] and the double-shear creep of pure Pb (99.999 wt%) [14]. As suggested by Chiang and Li [13], these sudden jumps were due to local recrystallization underneath the punch to release the internal stresses created by the impression; and the recrystallization did not have any significant effect on the steady state impression velocity (creep rate) for the steady state impression creep.…”
Section: Impression Creep Curvessupporting
confidence: 61%
See 1 more Smart Citation
“…After a short transient stage due to elastoplastic deformation, the impression creep reaches a steady state similar to the compression creep test with sudden jumps in the impression curves during the steady state impression creep. The sudden jumps in the impression curves are similar to that for the impression creep of single crystal Pb without the passing of electric current [13] and the double-shear creep of pure Pb (99.999 wt%) [14]. As suggested by Chiang and Li [13], these sudden jumps were due to local recrystallization underneath the punch to release the internal stresses created by the impression; and the recrystallization did not have any significant effect on the steady state impression velocity (creep rate) for the steady state impression creep.…”
Section: Impression Creep Curvessupporting
confidence: 61%
“…Mohamed and his co-workers [14] in their recent study of the double-shear of pure Pb found that the occurrence of the sudden jumps in the creep curves depends on the purity of Pb. They showed that there were periodic jumps for the double-shear creep of pure Pb with purity of 99.999 wt% and no jumps for the doubleshear creep of pure Pb with purity of 99.9 wt%.…”
Section: Impression Creep Curvesmentioning
confidence: 99%
“…More recently, commercially pure lead (99.95%) and high-purity lead (99.999%) of large, uniform grain sizes were creep tested at around 573 K [25]. However, with the 99.999% Pb, periodic accelerations giving faster overall creep rates as a result of dynamic recrystallization provided n values of 3 rather than 1.…”
Section: Creep Of Pure Aluminiummentioning
confidence: 99%
“…Once again, with the 99.95% Pb, periodic accelerations in creep rate were not found, giving lower measured creep rates. On this basis, it was concluded that the linear stress dependence thought to characterize Harper-Dorn creep is probably a direct consequence of making short-term measurements involving total creep strains less than 0.01 [25].…”
Section: Creep Of Pure Aluminiummentioning
confidence: 99%
“…The overall viscosity adds inversely since the mechanisms operate in parallel. In one study, because of the large grain sizes and small stresses, van Orman (2004) suggested Harper-Dorn creep as the deformation mechanism, obtaining a Journal of Geophysical Research: Solid Earth 10.1002/2017JB014881 very low viscosity, 10 11 Pa s, but the existence of Harper-Dorn creep has been questioned (Blum et al, 2002;Karato, 2008), especially in materials that are not ultra pure (Cheng et al, 1999). They found that the bulk shear strength is about 60% less than previous estimates (Hemley et al, 1997), suggesting that lower stresses can result in dislocation creep and hence a lower viscosity.…”
Section: Discussionmentioning
confidence: 99%